Dualised training programmes on the Philippines : How can they be consolidated by increasing cost and benefit transparency? - Schwarz, Michael [Verfasser]; Wenzelmann, Felix [Verfasser]; Capistrano, Maricris v. [Verfasser] (My University, 2017)
"Companies have been involved in dual training in the Philippines since 1994. However their participation rate is minimal and the dual system of vocational education and training is not the focus of government stakeholders. Great-er transparency of costs and benefits relating to company training might contribute to initiating, and empirically justifying, education policy deci-sion-making which is specifically targeted at consolidating this qualification pathway. The article introduces key finds from the cost-benefit analysis as well as survey results which are considered in terms of recommendations for the next steps in the conclusion." (author's abstract ; BIBB-Doku)
Dualisierte Ausbildungsprogramme auf den Philippinen
Keywords: S System beruflicher Bildung; I 2.3.4 Asien; Berufsbildungssystem; Berufsausbildung; Programm; Philippinen